Synergistic relationship of endophyte-nanomaterials to alleviate abiotic stress in plants - Adeleke, Bartholomew Saanu; Akinola, Saheed Adekunle; Adedayo, Afeez Adesina; Glick, Bernard R.; Babalola, Olubukola Oluranti (Frontiers in Environmental Science, 2022)
Plant responses to abiotic stresses through diverse mechanisms and strategic measures in utilizing nanomaterials have positively impacted crop productivity. Stress can cause membrane depletion, reactive oxygen species formation, cell toxicity and death, and reduction in plant growth. However, nanomaterials can mitigate some of the negative impacts of abiotic stresses and enhance crop yield. Some endophytic microbes can synthesize nanomaterials, which can maintain and enhance plant health and growth via nitrogen fixation, siderophore production, phytohormones synthesis, and enzyme production without any pathological effects. Nanoparticle-synthesizing endophytes also help boost plant biochemical and physiological functions by ameliorating the impact of abiotic stresses. The increase in the use and implementation of nano-growth enhancers from beneficial microbes, such as nano-biofertilizers, nano-pesticides, nano-herbicides, and nano-fungicides are considered safe and eco-friendly in ensuring sustainable agriculture and reduction of agrochemical usage. Promisingly, nanotechnology concepts in agriculture aim to sustain plant health and protect plants from oxidative stresses through the activation of anti-oxidative enzymes. The mechanisms and the use of nanomaterials to relieve abiotic plant stress still require further discussion in the literature. Therefore, this review is focused on endophytic microbes, the induction of abiotic stress tolerance in plants, and the use of nanomaterials to relieve abiotic plant stresses.